SOCIAL PRACTICE OF PEDAGANG ACUNG (VENDORS) AT KINTAMANI TOURIST AREA, BANGLI, BALI - Widiastini, Ni Made Ary; Ardika, I Wayan; Astawa, Nengah Dasi; Mudana, I Gede (E-Journal of Cultural Studies, 2016)
This present study is intended to explain the social practice performed by the pedagang acung (vendors) at Kintamani Tourist Area, Bangli Regency, Bali Province. In selling their commodities, the vendors cannot be separated from those who are involved in the development of tourism. In this present study the data were collected through observation, interview and library research. The data were eclectically analyzed using the theory of social practice and some other supporting theories. Such theories were used to identify various forms of the social practice performed by the vendors. The result of the study showed that in practice the vendors interacted with various parties involved in the development of tourism at Kintamani, Bangli. The consequence was that they fought for the capital as they had different interests. Having a limited amount of capital caused them to be marginalized by those who had bigger amounts of capital. The economic, social and cultural capitals they had caused them to be suspected of the sources of the problems in the development of tourism at Kintamani. They should not have been negatively viewed but should also have been positively viewed. In other words, they should have been viewed as those who ran entrepreneurship with limited amounts of capital who could also reduce the rate of unemployment and contribute to the economic development in Bangli Regency in particular and Bali Province in general.